2018
DOI: 10.1155/2018/3071959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexmedetomidine Postconditioning on Myocardial Ischemia/Reperfusion Injury in Diabetic Rats: Role of the PI3K/Akt-Dependent Signaling Pathway

Abstract: Objective The present study was designed to determine whether dexmedetomidine (DEX) exerts cardioprotection against myocardial I/R injury in diabetic hearts and the mechanisms involved. Methods A total of 30 diabetic rats induced by high-glucose-fat diet and streptozotocin (STZ) were randomly assigned to five groups: diabetic sham-operated group (DM-S), diabetic I/R group (DM-I/R), diabetic DEX group (DM-D), diabetic DEX + Wort group (DM-DW), and diabetic Wort group (DM-W). Another 12 age-matched male normal S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 42 publications
5
45
0
1
Order By: Relevance
“…In these cases, Dex used during and after the surgery likely makes some influence on the growth and invasion of glioma. 14,19 The present study showed an increase in phosphorylation levels of Akt, and ERK1/2 in glioma cells after exposure to Dex. Earlier research has shown that treatment with Dex is associated with an increase in [3H]thymidine incorporation into breast cancer cells and inhibition of cell death, suggesting that Dex stimulates proliferation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In these cases, Dex used during and after the surgery likely makes some influence on the growth and invasion of glioma. 14,19 The present study showed an increase in phosphorylation levels of Akt, and ERK1/2 in glioma cells after exposure to Dex. Earlier research has shown that treatment with Dex is associated with an increase in [3H]thymidine incorporation into breast cancer cells and inhibition of cell death, suggesting that Dex stimulates proliferation.…”
Section: Discussionsupporting
confidence: 55%
“…Cell proliferation induced by Dex may be related to the observed activation of PI3K, Akt and ERK1/2, the signalling molecules downstream of α 2 -ARs. 14,19 The present study showed an increase in phosphorylation levels of Akt, and ERK1/2 in glioma cells after exposure to Dex. The effects of Dex on the proliferation of various tumour hence deserve attention.…”
Section: Discussionsupporting
confidence: 55%
“…Although data reveal no differences at this time that are consistent with I–R intolerance, exaggerated injury with T2D could involve differences pre‐ischaemia (influencing propensity to subsequent cell injury/death). There is evidence of changes in baseline Bcl2 proteins in models of T2D, differences that may be maintained or lost with I–R (Cheng et al., ). Findings are equivocal regarding baseline phospho‐AKT, including evidence of no change (Cheng et al., ; Desrois et al., ), reductions (Chen et al., ) or increases (Bouhidel et al., ; Cook et al., ) in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of changes in baseline Bcl2 proteins in models of T2D, differences that may be maintained or lost with I–R (Cheng et al., ). Findings are equivocal regarding baseline phospho‐AKT, including evidence of no change (Cheng et al., ; Desrois et al., ), reductions (Chen et al., ) or increases (Bouhidel et al., ; Cook et al., ) in T2D. Although post‐ischaemic AKT phosphorylation was unaltered by diabetes (Figure ), it is possible earlier inhibitory or stimulatory impacts of T2D may normalise by 45 min reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia, characterized by a pathological condition, lacks blood supply to the heart . Myocardial ischemia/reperfusion (I/R), known to restore blood supply to ischemic area, causes further damage such as oxidative stress, arrhythmia, cell apoptosis, and cell death . Hypoxia/reoxygenation (H/R) is an important pathological process in the I/R phase of acute myocardial infarction .…”
Section: Introductionmentioning
confidence: 99%